1998
DOI: 10.1098/rspb.1998.0559
|View full text |Cite
|
Sign up to set email alerts
|

Parasite–induced risk of mortality elevates reproductive effort in male Drosophila

Abstract: A trade-off between sex and somatic maintenance is fundamental to life-history theory. Tests of this trade-off usually emphasize deleterious consequences of increased reproduction on life span. Here we show the reverse effect, that reductions in the expected life span elevate sexual activity. Experimentally parasitized male Drosophila nigrospiracula lived shorter lives, but before dying, they courted females significantly more than unparasitized controls. This greater courtship resulted in increased mating spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
128
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 26 publications
5
128
2
1
Order By: Relevance
“…A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18]. In our study, however, calling activity did not increase in all infected frogs; we found that infected frogs in relatively poor condition were less likely to call than uninfected frogs.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18]. In our study, however, calling activity did not increase in all infected frogs; we found that infected frogs in relatively poor condition were less likely to call than uninfected frogs.…”
Section: Discussioncontrasting
confidence: 50%
“…For example, among female hosts, Tasmanian devils (Sarcophilus harrisii) infected by a transmissible cancer mature and breed earlier [12], and crickets (Acheta domesticus) infected by a bacterium, and water fleas (Daphnia magna) infected by a microsporidian lay more eggs [13,14]. Among male hosts, frogs (Lithobates pipiens) infected by a fungus increase sperm production [15], flies (Drosophila nigrospiracula) infected by a parasitic mite, and amphipods (Corophium volutator) infected by trematodes increase reproductive effort [16,17], and beetles (Tenebrio molitor) infected by tapeworms provide higher quality nuptial gifts to their mates, thus increasing egg production [18]. Whether hosts increase their reproductive effort in response to an infection depends on many factors, including resource availability [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, parasite-induced risk of mortality may also increase reproductive effort (e.g. Polak & Starmer 1998). Numerous animals harbour endoparasites or endosymbionts which gain transmission to a new host generation via female eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Polak & Starmer 1998;Altizer & Oberhauser 1999;Bollache et al 2002), with different mechanisms and proximate or ultimate causes (Worden et al 2000;Combes 2001;Hurd 2001). In some cases, parasites decrease the reproductive effort of their hosts as host resources are reallocated to parasites (Combes 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rate is not only affected by intrinsic factors such as age but also by extrinsic factors such as predation, food shortage, and parasitism. Infection may be a good indicator of a rapidly diminishing life span (Grenfell and Dobson 1995), and both theoretical and empirical work has shown that parasitized hosts can adaptively adjust their life-history traits to reduce the cost of parasitism (Minchella and LoVerde 1981;Hochberg et al 1992;Forbes 1993;Lafferty 1993;Polak and Starmer 1998;Adamo 1999;Agnew et al 2000;McCurdy 2000). For instance, Biomphalaria glabrata snails underwent a reproductive burst immediately following exposure to Schistosoma mansoni (Minchella and LoVerde 1981).…”
mentioning
confidence: 99%